New transition metal complexes containing imidazole rings endowed with potential antiamoebic activity. Issue 5 (23rd March 2016) - Wani, Mohmmad Younus; Bhat, Abdul Roouf; Azam, Amir; Athar, Fareeda; Sobral, Abilio J. F. N.
Abstract : Imidazole-hydrazones were found to be better antiamoebic lead molecules compared to the standard drug metronidazole (MNZ ). Chelation of these bioactive ligands with metals enhanced their activity profiles. Abstract : A useful concept for the rational design of anti-protozoal drug candidates is the complexation of bioactive ligands with transition metals. We previously reported that nitroimidazole acylhydrazones possess excellent antiamoebic activity; in this study, we synthesized some Cu II, Co II and Ni II metal complexes and chose 2-(5-methyl-2-nitro-1 H -imidazol-1-yl)- N ′-[( E )-pyridin-2-ylmethylidene]acetohydrazide as a ligand. Physical and spectroscopic characterization revealed a distorted octahedral geometry for the complexes. The pharmacological characterization, including assays against Entamoeba histolytica and cytotoxicity to mammalian cells, revealed that chelation improves the antiamoebic activity of the ligand. Docking of the ligand with thioredoxin reductase (EhTrR), a promising target for the treatment of amoebiasis, showed that the inhibitor snugly fits the active site of the target enzyme, which may well explain the excellent inhibitory activity.